EXPOART: análise sobre gênero no contexto da produção do artesanato do bordado ponto cruz e seu reflexo nas disciplinas de artes visuais - GUIDA, José de Lourdes Soares (2023)
This article deals with a pedagogical proposal entitled "Expoart: analysis of gender in the context of cross-stitch embroidery craft production and its reflection in the visual arts discipline", held at the Abrahão Martins Integrated Unit, located in the municipality of Loreto-MA. The research is aligned with Teaching, Learning and Mediation Processes in Arts and aims to describe the possible contributions of the cross-stitch embroidery technique, as a modality of visual art, in combating the prejudice of gender difference within Art classrooms. The methodology is quantitative-qualitative and has as main references, for the guiding construction of the proposal, the BNCC (2017), which guarantees that the student must both flow and value cultural experiences; Castells (2018) states that, in fact, an awareness of the patriarchal culture within the school space is necessary, since the school made a separation by sex several moments in its trajectory. In the development of this proposal, dialogue was sought so that cross stitch embroidery in the living room can inhibit stereotypes about the male gender not being able to exercise the profession of manual arts and the culmination was worked on an exhibition, called Expoart.